Faculty learning communities : working towards a more equitable, just, and antiracist future in higher education - Rainville, Kristin N.; Desrochers, Cynthia G.; Title, David G. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"This edited book on Faculty Learning Communities (FLCs) provides and explores powerful examples of FLCs as a impactful form of professional learning for faculty in higher education. The chapters describe faculty learning community initiatives focused on diversity, equity, and belonging in higher education. Contributing authors provide a framework for faculty learning communities and how these communities can offer faculty a place and space to explored antiracist and social justice-oriented teaching. show the impact of faculty learning communities on teaching practices or student learning, and describe how these communities of practice can lead to institutional change. The book's foreword, by Milton D. Cox, investigates the past and future of faculty learning communities focused on diversity and equity"-- Provided by publisher.
Keywords: Professional learning communities.; Communities of practice.; College teachers -- Professional relationships.; Social justice and education.; Anti-racism.; Education -- Professional Development.; Teacher training.; elektronické knihy; electronic books